2018
DOI: 10.1128/jb.00508-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screens Reveal New Gene Products That Influence Genetic Competence in Streptococcus mutans

Abstract: A network of genes and at least two peptide signaling molecules tightly control when becomes competent to take up DNA from its environment. Widespread changes in the expression of genes occur when is presented with competence signal peptides , including increased production of the alternative sigma factor, ComX, which activates late competence genes. Still, the way that gene products that are regulated by competence peptides influence DNA uptake and cellular physiology are not well understood. Here, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…While the identity of the sugar being transferred is not currently known, it is reminiscent of the activity of the glucosyltransferases RgpE and RgpH in S. mutans. Studies of RgpI have shown that it plays a role in comX-inducing peptide (XIP)-mediated activation of the alternative sigma factor comX (48). ComX, a protein that guides RNA polymerase to the promoters of late competence genes (49) and facilitates their transcription, is not activated in the absence of rgpI, rendering those strains nontransformable in defined medium containing XIP (48).…”
Section: Figmentioning
confidence: 99%
“…While the identity of the sugar being transferred is not currently known, it is reminiscent of the activity of the glucosyltransferases RgpE and RgpH in S. mutans. Studies of RgpI have shown that it plays a role in comX-inducing peptide (XIP)-mediated activation of the alternative sigma factor comX (48). ComX, a protein that guides RNA polymerase to the promoters of late competence genes (49) and facilitates their transcription, is not activated in the absence of rgpI, rendering those strains nontransformable in defined medium containing XIP (48).…”
Section: Figmentioning
confidence: 99%
“…Tn-seq technologies have been applied in Streptococcus pneumoniae ( 11 ), Streptococcus pyogenes ( 17 ), and Streptococcus agalactiae ( 18 ). It is only recently that this approach has been applied to the study of S. mutans ( 19 ), with a focus on genetic competence.…”
Section: Introductionmentioning
confidence: 99%
“…Natural competence for DNA transformation is one of the main strategies employed by streptococci to acquire exogenous DNA for genetic diversity (Kreth et al , ; Croucher et al , ; Lin et al , ; Wholey et al , ; Underhill et al , ). First described in S. pneumoniae (Avery et al , ), natural competence has been found in more than 80 bacterial species to date, particularly in oral streptococci (Johnston et al , ; Khan et al , ; Salvadori et al , ; Shields et al , ). Internalization of extracellular DNA greatly contributes to the genomic plasticity of bacteria, but this also increases the risk of deleterious mutations and consumes energy for competence machinery synthesis (Croucher et al , ).…”
Section: Introductionmentioning
confidence: 99%